Lack of association between synapsin II (SYN2) gene polymorphism and susceptibility epilepsy: a case-control study and meta-analysis - Haerian, B.S.; Lim, K.S.; Tan, H.J.; Wong, C.P.; Wong, S.W.; Tan, C.T.; Raymond, A.A.; Mohamed, Z. (2011)
Objective: The SYN2 rs3773364 A>G polymorphism has been proposed to be involved in susceptibility to epilepsy, but research results have been inconclusive. The aim of this study was to investigate the association between the SYN2 rs3773364 A>G polymorphism and susceptibility against epilepsy in a case-control study and a meta-analysis. Methods: The SYN2 rs3773364 A>G polymorphism was successfully genotyped in 1182 samples (618 epilepsy patients) of Chinese, Indian, and Malay ethnicities. Meta-analysis of the related studies, including this case-control study, was performed under alternative genetic models. Results: Data from the case-control study indicated no allelic and genotypic association of this locus with susceptibility to epilepsy in the tri-ethnic Malaysian population. Similar finding was obtained by stratified analysis by epilepsy syndrome for idiopathic epilepsy. These results were verified by meta-analysis of the related pooled data. Conclusions: Our study indicated that SYN2 rs3773364 A>G polymorphism is not a risk factor for susceptibility to epilepsy. Synapse 2011. Â© 2011 Wiley-Liss, Inc.